Liver enzyme levels in adolescents with obesity and insulin resistance: a propensity score matching analysis - Miguel A. Villasís-Keever; Jessie N. Zurita-Cruz; Karla D. Nava-Sanchez; Aly S. Barradas-Vázquez; Ana L. López-Beltran; Mireya E. Espíritu-Díaz; Martha A. Delgadillo-Ruano (Permanyer, 2024)
Background: Elevated liver enzyme levels have been associated with metabolic syndrome in both obese and non-obese pediatric populations. This study aims to compare the serum liver enzyme levels in obese adolescents with and without insulin resistance (IR). Methods: A cross-sectional analysis was conducted involving obese adolescents aged 10-18. We assessed somatometry, serum insulin levels, lipid profiles, and liver enzymes (aspartate aminotransferase [AST], alanine aminotransferase [ALT], and gamma-glutamyl transferase [GGT]). Statistical differences between groups were evaluated using Student's t-test or the Chi-squared test, with IR (wIR) status matched by propensity scores based on body mass index (BMI) z-scores. Results: The study included 365 adolescents with obesity, 229 wIR, and 136 without (woIR). Before matching, the wIR group had a significantly higher BMI z-score (2.21 vs. 2.14, p = 0.032). After matching for BMI z-scores (n = 122 each group), the wIR group displayed significantly higher levels of AST (32.3 vs. 24.7, p < 0.001) and ALT (42.4 vs. 30.9, p < 0.001), but no significant differences were observed in GGT levels (37.4 vs. 32.5, p = 0.855). Conclusion: Obese adolescent's wIR exhibit higher serum ALT and AST levels, suggesting that altered AST is a potential risk factor for IR.